The portfolio theory of inflation and policy (in)effectiveness - Biagio Bossone (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
The analysis of open macroeconomies typically assumes (implicitly or explicitly) that resource allocation decisions are taken by domestic agents. The Portfolio Theory of Inflation (PTI) developed in this study assumes that some critical allocation decisions are taken by global investors and investigates how such decisions affect the effectiveness of macroeconomic policy in open and highly financially integrated economies. The PTI adopts a modified version of the portfolio balance approach to exchange rate determination and incorporates optimal intertemporal choices from global investors who allocate resources internationally based, inter alia, on the perceived policy credibility of the national authorities and their policies. The PTI shows that when a country has low credibility and is heavily indebted, investors hold its economy to a tighter intertemporal budget constraint and policies aimed to stimulate output growth do in fact dissipate into currency depreciation and higher inflation, with limited or no impact on output. On the other hand, high credibility creates space for effective and non-inflationary macro policies with limited impact on nominal variables.
Keywords: E31; E4; E5; E62; F31; G15; H3; 330; credibility; exchange rate; financial integration; global investor; interest rate; intertemporal budget constraint; money; bonds and assets; pass-through